Clodronate Treatment Prevents Vaginal Hypersensitivity in a Mouse Model of Vestibulodynia - Castro, Joel; Harrington, Andrea M.; Chegini, Fariba; Matusica, Dusan; Spencer, Nick J.; Brierley, Stuart M.; Haberberger, Rainer V.; Barry, Christine M. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Improved understanding of vestibulodynia pathophysiology is required to develop appropriately targeted treatments. Established features include vulvovaginal hyperinnervation, increased nociceptive signalling and hypersensitivity. Emerging evidence indicates macrophage-neuron signalling contributes to chronic pain pathophysiology. Macrophages are broadly classified as M1 or M2, demonstrating pro-nociceptive or anti-nociceptive effects respectively. This study investigates the impact of clodronate liposomes, a macrophage depleting agent, on nociceptive signalling in a mouse model of vestibulodynia. Methods Microinjection of complete Freund’s adjuvant (CFA) at the vaginal introitus induced mild chronic inflammation in C57Bl/6J mice. A subgroup was treated with the macrophage depleting agent clodronate. Control mice received saline. After 7 days, immunolabelling for PGP9.5, F4/80+CD11c+ and F4/80+CD206+ was used to compare innervation density and presence of M1 and M2 macrophages respectively in experimental groups. Nociceptive signalling evoked by vaginal distension was assessed using immunolabelling for phosphorylated MAP extracellular signal-related kinase (pERK) in spinal cord sections. Hyperalgesia was assessed by visceromotor response to graded vaginal distension. Results CFA led to increased vaginal innervation (p < 0.05), increased pERK-immunoreactive spinal cord dorsal horn neurons evoked by vaginal-distension (p < 0.01) and enhanced visceromotor responses compared control mice (p < 0.01). Clodronate did not reduce vaginal hyperinnervation but significantly reduced the abundance of M1 and M2 vaginal macrophages and restored vaginal nociceptive signalling and vaginal sensitivity to that of healthy control animals. Conclusions We have developed a robust mouse model of vestibulodynia that demonstrates vaginal hyperinnervation, enhanced nociceptive signalling, hyperalgesia and allodynia. Macrophages contribute to hypersensitivity in this model. Macrophage-sensory neuron signalling pathways may present useful pathophysiological targets.